АНТИБАКТЕРИАЛЬНАЯ ТЕРАПИЯ ТЯЖЕЛОЙ ВНЕБОЛЬНИЧНОЙ ПНЕВМОНИИ У ВЗРОСЛЫХ: ОБЗОР РЕКОМЕНДАЦИЙ И КЛИНИЧЕСКИЕ ПРИМЕРЫ - С. А. Рачина; Р. С. Козлов; Н. Н. Дехнич; А. А. Бобылев; О. Д. Барашко (Архивъ внутренней медицины, 2015)
This article is a review of modern views on etiology of severe community-acquired pneumonia, resistance to antibiotics and key bacterial agents. We observe recommendations on antibiotic choose in different situations in adults. We provide descriptions of several clinical cases of severe pneumonia, caused by different bacterial agents.